Optimization of Organic Waste Management in Garahan Village Through EM4 Application: Evaluation of Its Effectiveness in Producing Compost - Alissa Ernawati Adisiswanto; Dili Prelina Nugraini (Indonesian Journal of Community Services Cel, 2025)
Background: Organic waste management in rural areas remains a significant challenge, where household and agricultural waste accounts for approximately 65% of total waste volume, contributing to environmental degradation and increasing greenhouse gas emissions.Aims: This Community Service Program aimed to evaluate the effectiveness of Effective Microorganisms 4 (EM4) in converting organic waste into compost in Garahan Village, Silo District, Jember Regency.Methods: The program employed a Participatory Action Research (PAR) approach involving 50 households. Data were collected through observations, interviews, and physicochemical analyses conducted during a 21-day fermentation process consisting of anaerobic and aerobic stages.Results: The results demonstrated that the application of EM4 significantly enhanced the waste decomposition process. The final compost achieved a stable temperature of 35°C on the third day, a neutral pH of 6.8, a nitrogen content of 1.8%, and a C/N ratio of 25:1. The program reduced waste volume by 65%, achieved an 85% community participation rate, and produced compost that met the SNI 19-7030-2004 standard. These findings support the implementation of a sustainable bioremediation model that reduces reliance on chemical fertilizers and contributes to the achievement of SDGs 11 and 12.